2010
DOI: 10.1245/s10434-010-1025-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification for Early Esophageal Adenocarcinoma: Analysis of Lymphatic Spread and Prognostic Factors

Abstract: Risk stratification is possible for patents with T1 esophageal adenocarcinoma. Local resection techniques without lymphadenectomy may be alternatives for T1a tumors. Esophagectomy should remain the standard of care for patients with T1b tumors and those with LVI or poor differentiation considered for neoadjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
87
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 60 publications
13
87
0
Order By: Relevance
“…It is hard to identify patients with high risk of lymph node metastases in mucosal tumor in our study as only one of the 62 patients with mucosal tumor had lymph node metastases (1.6%). According to the previous reports (Ancona et al, 2008;Barbour et al, 2010) and our finding, histologic grade was another factor associated with lymph node metastases in EEC. We think that for patients with poor differentiated mucosal tumors, careful selection should be made for patients to receive endoscopic treatment.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…It is hard to identify patients with high risk of lymph node metastases in mucosal tumor in our study as only one of the 62 patients with mucosal tumor had lymph node metastases (1.6%). According to the previous reports (Ancona et al, 2008;Barbour et al, 2010) and our finding, histologic grade was another factor associated with lymph node metastases in EEC. We think that for patients with poor differentiated mucosal tumors, careful selection should be made for patients to receive endoscopic treatment.…”
Section: Discussionsupporting
confidence: 75%
“…The number of metastatic lymph nodes has also been shown to be one of the most important independent prognostic factors for patients with esophageal cancer after curative resection (Rice et al, 2009;Rice et al, 2010). Previous studies with EEC also showed that lymph node metastasis was a significant predictor for survival (Westerterp et al, 2005;Barbour et al, 2010); Natsugoe et al, 2004;Tajima et al, 2000;Grotenhuis et al, 2010). In our study, although the 5-and 10-year overall survival rates of 83.0% and 71.8% for pN0 category patients were higher than those of 67.2% and 56.0% for pN+ category patients, the difference was not statistically significant (P=0.104).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations